Effect of strain rate and temperature on the deformation behavior in a Ti-23.1Nb-2.0Zr-1.0O titanium alloy. (20th May 2021) - Yang, Yi; Xu, Di; Cao, Sheng; Wu, Songquan; Zhu, Zhengwang; Wang, Hao; Li, Lei; Xin, Shewei; Qu, Lei; Huang, Aijun
Highlights: Compression behavior of a Ti-23.1Nb-2.0Zr-1.0O (at.%) alloy has been explode in a temperature range of 100−200 °C and a strain rate range of 0.1-1000 s −1 . Multiple deformation modes, including dislocation slip, 332〈113〉 twinning, 112〈111〉 twinning, stress-induced α" martensitic (SIMα") and stress-induced ω phase (SIω) transformations were observed at high strain rates and low deformation temperatures. Both twinning and SIω transformations prefer to be activated at low deformation temperatures and high strain rates. Abstract: The compression behavior of a Ti-23.1Nb-2.0Zr-1.0O (at.%) alloy was investigated at strain rates from 0.1 s −1 to 1000 s −1 and temperatures from 100 °C to 200 °C on a Gleeble 3800 system and Split Hopkinson Pressure Bar (SHPB) compressive tester. Optical microscopy, electron backscatter diffraction (EBSD), X-ray diffraction (XRD) and transmission electron microscopy (TEM) were employed to characterize the microstructure evolution during the deformation. Numerous deformation phenomena, including dislocation slip, twinning of both 332〈113〉 and 112〈111〉 modes, stress-induced α" martensite (SIMα") and stress-induced ω (SIω) transformations, were observed. The preferred activation of twinning and SIω transformations was observed in the sample compressed at lower temperatures and/or higher strain rates. The underlying mechanism is that twinning and stress induced phase transformations are attribute to higher stress concentrations at β grain boundaries and additional energy supplied by a higher strain rate, as well as high stacking fault energy because of higher temperature.